Women improving nutrition through self-help groups in India: Does nutrition information help? - Kumar, Neha; Raghunathan, Kalyani; Quisumbing, Agnes R.; Scott, Samuel P.; Menon, Purnima; Thai, Giang; Gupta, Shivani; Nichols, Carly; WINGS study team (Elsevier, 2024)
Women’s self-help groups (SHGs) are an important platform for reaching poor women in India. Despite SHGs' women-focused programming, evidence of the impact of SHG-based interventions on nutrition outcomes is limited, and most evaluations of nutrition interventions have not examined intermediate outcomes along the impact pathways or outcomes for women themselves. This paper evaluates the effectiveness of an integrated agriculture-nutrition intervention delivered through women’s SHGs in five states in central and eastern India. The interventions involved the delivery of nutrition behavior change communication to groups through participatory approaches, community engagement around key issues, and the strengthening of collective organizations. Our analysis is based on three rounds of rich panel data on close to 2700 rural women and their households from eight districts in these five states and qualitative work from an accompanying process evaluation. Using difference-in-difference models with nearest neighbor matching methods, we present results on women’s anthropometry and diet-related outcomes.